PENGARUH KARAKTERISTIK INDIVIDU KOMUNIKASI INTERNAL DAN LINGKUNGAN KERJA TERHADAP ETOS KERJA PEGAWAI PADA BADAN PENDAPATAN DAERAH KABUPATEN ASAHAN - Bayu Anggara; Dian Wahyuni (Smart Education, 2026)
This study aims to determine the simultaneous and partial effects of individual characteristics, internal communication, and work environment on work ethic. This research is a quantitative descriptive study, utilizing multiple linear regression for data analysis. The sampling technique employed was saturated sampling, involving 68 respondents. Validity and reliability tests were conducted to ensure the research instrument's adequacy. The multiple linear regression analysis yielded the equation: Y = 4.597 + 0.282X1 + 0.497X2 + 0.146X3. The F-test results demonstrate that H1 is accepted and H0 is rejected, indicating that individual characteristics, internal communication, and work environment simultaneously influence work ethic, with an Fvalue (12.575) > Ftable (2.75). The t-test results prove that, partially, individual characteristics have a positive and significant effect on work ethic with a tvalue (4.643) > ttable (1.99714); internal communication has a positive and significant effect on work ethic with a tvalue (3.635) > ttable (1.99714); and work environment has a positive and significant effect on work ethic with a tvalue (3.668) > ttable (1.99714). Based on the tvalues, individual characteristics emerged as the most dominant factor influencing work ethic. The R-squared test results show an adjusted R-square value of 0.541, explaining that the contribution of individual characteristics, internal communication, and work environment to work ethic is 54.1%, while the remaining 45.9% is influenced by other factors not examined in this study.